Trade Conflicts Between China and the USA Opportunities and Challenges - Zhang Xiaoling (2021)
As the two largest economies in the world, the results of trade Conflicts between China and the United States not only affect their respective national economy, but also affect the world pattern extremely profoundly. As soon as the China-US trade war started, it attracted great attention and discussion around the world. In the past two years, foreign scholars have carried out research on the China-US trade war and produced a series of research results. The thesis is based on the theories of protectionism, trade conflicts and international competitiveness. Through combing of the literature, it could be found that protectionism is a important tool for the countries to improve their international competitiveness, however the protectionism could cause the trade conflicts which in turn will exert effect on the competitiveness of these nations. Thus, make clear the deep roots of China-US conflicts could help to improve the current sever situation and promote the global development. The relationship between China and the USA has gone through many ups and downs. The trade conflicts has always been existing through the detailed historical review of the trade and economic relations between China and the USA. However, since tariff actions taken by President Trump in 2018, in order to realize “Make America Great Again”, the trade conflicts were gradually evolved into the trade war, rounds of conversations were also conducted. Even the first phase agreement was achieved, the common sense has been received so far which means the conflicts still exist. By looking into the origin, high trade imbalance, rising protectionism and the leadership competition should be considered as the major causes. By taking empirical studies, current status of foreign trade, trade protectionism and specific industries shall be presented. The huge asymmetry and increasing number of trade barriers all add unknown factors to the situation in terms of the economic and trade development. USA was also trying its best to contain the development of China which could be seen from the case of Huawei. The “USA First” idea has always been the deep inspiration of its protectionism. The spillover effects could also be easily seen during the trade war between China and USA. Combing the current background of COVID-19, a lot of challenges could be seen, especially for USA. Tariff policies and large-scale unemployment will somehow curb consumption growth thus become the obstacles. USA is suffering a lot due to the spread of the epidemic while China has controlled perfectly which also gave China great opportunities. Rise of domestic market and consumption in China, digitization and technological upgrading and favorable macro policies all push China stepping into a high-quality development way. By analyzing the competitiveness of China digital trade, the great potential in this field will also become a powerful point for China in the future. Above all, in order to achieve win-win results. China and the USA must cool down, and establish negotiations as soon as possible. There are several developing possibilities in the future, like G0, G2 and so on, which is quiet unpredictable. However, what could be certain is that only by cooperation, a better global development pattern could be formed.